(untitled) (Bangladesh Journal of Microbiology, 2008)
The present study was carried out to assess the total bacterial load, incidence of total coliform, faecal coliform (Escherichia coli) and Salmonella species in water and soil of a tannery polluted environment (river Buriganga) and a selected freshwater fish pond environment. Samples were analyzed for their monthly variation and made a comparative investigation between the two different environments. The highest viable bacterial count was observed in tannery polluted water (2.7 x 105 cfu/ml) in May 2005 and in soil (5.7 x 107 cfu/g) in August, 2005. The total coliform and faecal coliform counts were always very high (>2,400/100 ml) in water and soil (>240/g) of tannery polluted area as measured by the most probable number (MPN) method. Salmonella was always present in tannery polluted samples, and occasionally in fresh water pond samples. It was also observed that tannery polluted environment was heavily polluted due to presence of large number of pathogenic bacteria as a result of tannery wastes discharged into the area. This poses serious threats to aquatic organisms, especially fish, and also for human being living in the Hazaribagh area. Keywords: Bacterial flora, Tannery polluted environment, Freshwater fish pond DOI: http://dx.doi.org/10.3329/bjm.v24i2.1264